Novel aspects of RNA regulation in Staphylococcus aureus. Issue 15 (27th May 2014) - Fechter, Pierre; Caldelari, Isabelle; Lioliou, Efthimia; Romby, Pascale
Abstract : A plethora of RNAs with regulatory functions has been discovered in many non‐pathogenic and pathogenic bacteria. In Staphylococcus aureus, recent findings show that a large variety of RNAs control target gene expression by diverse mechanisms and many of them are expressed in response to specific internal or external signals. These RNAs comprise trans ‐acting RNAs, which regulate gene expression through binding with mRNAs, and cis ‐acting regulatory regions of mRNAs. Some of them possess multiple functions and encode small but functional peptides. In this review, we will present several examples of RNAs regulating pathogenesis, antibiotic resistance, and host‐pathogen interactions and will illustrate how regulatory proteins and RNAs form complex regulatory circuits to express the virulence factors in a dynamic manner.